Towards an Ethological Animal Model of Depression? A Study on Horses - Fureix, Carole; Jego, Patrick; Henry, Séverine; Lansade, Léa; Hausberger, Martine (PLOS ONE, 2012)
Background Recent reviews question current animal models of depression and emphasise the need for ethological models of mood disorders based on animals living under natural conditions. Domestic horses encounter chronic stress, including potential stress at work, which can induce behavioural disorders (e.g. “apathy”). Our pioneering study evaluated the potential of domestic horses in their usual environment to become an ethological model of depression by testing this models’ face validity (i.e. behavioural similarity with descriptions of human depressive states). Methodology/Principal Findings We observed the spontaneous behaviour of 59 working horses in their home environment, focusing on immobility bouts of apparent unresponsiveness when horses displayed an atypical posture (termed withdrawn hereafter), evaluated their responsiveness to their environment and their anxiety levels, and analysed cortisol levels. Twenty-four percent of the horses presented the withdrawn posture, also characterized by gaze, head and ears fixity, a profile that suggests a spontaneous expression of “behavioural despair”. When compared with control “non-withdrawn” horses from the same stable, withdrawn horses appeared more indifferent to environmental stimuli in their home environment but reacted more emotionally in more challenging situations. They exhibited lower plasma cortisol levels. Withdrawn horses all belonged to the same breed and females were over-represented. Conclusions/Significance Horse might be a useful potential candidate for an animal model of depression. Face validity of this model appeared good, and potential genetic input and high prevalence of these disorders in females add to the convergence. At a time when current animal models of depression are questioned and the need for novel models is expressed, this study suggests that novel models and biomarkers could emerge from ethological approaches in home environments.